Bilateral recurrent macular holes - Yoon, Stephen P. (Am J Ophthalmol Case Rep, 2018)
PURPOSE: To report an unusual case of bilateral recurrent full-thickness macular holes (FTMH) in both eyes of a single patient over a 15-year period, with a total of 3 FTMH in the right eye and 2 in the left eye. Each FTMH was successfully treated with vitreous surgery, resulting in hole closure and visual acuity improvement. OBSERVATIONS: During the previous 15 years, a 59-year-old female developed a total of 3 FTMH in the right eye and 2 FTMH in the left eye. The initial FTMH in each eye was surgically closed with pars plana vitrectomy (PPV), epiretinal membrane (ERM) peeling, 14% C(3)F(8) gas placement, and face down positioning. Subsequent recurrences of FTMH, 2 in the right and 1 in the left, were surgically closed with PPV and ERM peeling and/or indocyanine green-assisted internal limiting membrane peeling, 14% C(3)F(8) gas placement, and face down positioning. Seven years following the last FTMH surgical closure, the patient's best-corrected visual acuity was 20/50 in the right eye and 20/32 in the left eye with no FTMH in either eye. CONCLUSIONS AND IMPORTANCE: This case illustrates that a rare individual may have more than one recurrent FTMH in both eyes. Final visual outcome can be favorable following closure of more than one recurrent FTMH.